Designing Difference: A History of Interiors for Autism in Ireland, 1960- 2000 - Brien, Megan (Trinity College Dublin. School of Histories & Humanities. Discipline of History Of Art, 2025)
Traditionally, design practice has been seen as a problem-solving field, mirroring the historical view in psychiatry that pathologised autism as a behavioural issue and portrayed autistic individuals as `problems' needing `solutions.' This thesis examines the dynamics of this problem-solution relationship through a history of interiors for autism in Ireland from 1960 to 2000 - a period characterised by significant changes in the conceptualisation of autism within social, political, and medical discourse. It explores the tension between modernity and enclosed institutions, examining how and where autistic individuals, labelled as `patients,' received care when they did not conform to the established frameworks of hospitals, mental institutions, or county homes. It emphasises the interplay between physical environments and personal identity, particularly the identities of autistic individuals, who have been variously viewed as mentally ill, disabled, or neurodiverse throughout the twentieth century. This thesis seeks to disclose design's role in perpetuating narratives of normalcy and difference by examining how interiors have historically accommodated diverse identities and imposed frameworks upon them. Through this critical lens, the thesis explores how design choices, at both spatial and material levels, intersected with the evolving medical, social, and cultural understandings of autism throughout the twentieth century. By addressing these complexities, this thesis posits that interiors are far from passive backdrops. Rather it proposes that interiors shaped and were shaped by changing ideologies of care, policy, and design. Writing a history of interiors for autism raises significant methodological considerations regarding how to approach such a history; this thesis' methodology allows for an exploration of design schemes and interiors as ideological expressions of care philosophies whilst also addressing the material consequences of the limited lifespan of interior decoration.
APPROVED